Composition and characteristics of the ferromanganese crusts from the western Arctic Ocean - Konstantinova, Natalia (2018)
Layered ferromanganese crusts collected by dredge from a water depth range of 2770 to 2200 m on Mendeleev Ridge, Arctic Ocean, were analyzed for mineralogical and chemical compositions and dated using the excess 230Th technique. Comparison with crusts from other oceans reveals that Fe-Mn deposits of Mendeleev Ridge have the highest Fe/Mn ratios, are depleted in Mn, Co, and Ni, and enriched in Si and Al as well as some minor elements, Li, Th, Sc, As and V. However, the upper layer of the crusts shows Mn, Co, and Ni contents comparable to crusts from the Atlantic and Indian Oceans. Growth rates vary from 3.03 to 3.97 mm/Myr measured on the uppermost 2 mm. Mn and Fe oxyhydroxides (vernadite, ferroxyhyte, birnessite, todorokite and goethite) and nonmetalliferous detrital minerals characterize the Arctic crusts. Temporal changes in crust composition reflect changes in the depositional environment. Crust formation was dominated by three main processes: precipitation of Fe-Mn oxyhydroxides from ambient ocean water, sorption of metals by those Fe and Mn phases, and fluctuating but large inputs of terrigenous debris.